When Pandemic Hits: Exercise Frequency and Subjective Well-Being During COVID-19 Pandemic - Brand, Ralf; Timme, Sinika; Nosrat, Sanaz (Frontiers in Psychology, 2020)
The governmental lockdowns related to the COVID-19 pandemic have forced people to change their behavior in many ways including changes in exercise. We used this brief window of global lockdown as an opportunity to investigate the effects of externally imposed restrictions on exercise-related routines and related changes in subjective well-being. Statistical analyses are based on data from13,696 respondents in 18 countries using a cross-sectional online survey. A mixed effects modeling approach was used to analyze data. We built a prediction model, while controlling for national differences, to estimate changes in exercise frequency during similar lockdown conditions depending on pre-lockdown exercise frequency. We also tested whether exercise frequency before and during the pandemic would influence mood during the pandemic. According to the prediction model, those who rarely exercise before a lockdown tend to increase their exercise frequency during it, and those who are frequent exercisers before a lockdown tend to maintain it. The data show that those who exercised almost every day during this pandemic had the best mood, regardless of whether or not they exercised pre pandemic. Those who were inactive pre pandemic and slightly increased their exercise frequency during the pandemic, reported no change in mood compared to those who remained inactive during the pandemic. Those who reduced their exercise frequency during the pandemic reported worse mood compared to those who maintained or increased their pre-pandemic exercise frequency. This study also suggests that under similar lockdown conditions, about two thirds of those who never or rarely exercise before a lockdown might adopt an exercise behavior or increase their exercise frequency. However, such changes did not immediately result in improvement in subjective well-being. These results may inform national policies, as well as health behavior and exercise psychology research on the importance of exercise promotion, and prediction of changes in exercise behavior and its consequences on subjective well-being during future pandemics.